2010
DOI: 10.1007/s11099-010-0069-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the photosynthetic characteristics and photosystem stoichiometries in wild-type and Chl b-deficient mutant rice seedlings under various irradiances

Abstract: By using a wild-type rice (Oryza sativa L. cv. Norin No. 8) and the chlorophyll (Chl) b-deficient mutant derived from Norin No. 8 (chlorina 11), the present study monitored the oxygen evolution, contents of Chl a and b, β-carotene, and lutein in leaf and the contents of cytochrome f, and the reaction centres of photosystem I (PSI) and photosystem II (PSII) in thylakoids. The oxygen evolution, maximal quantum yield of PSII (F v /F m ) and Chl concentration remained constant in both Norin No. 8 and chlorina 11 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Alternatively, Štroch et al (2004) found that the substantial part of the xanthophyll cycle pigments in chlorina f2 mutant of barley was not bound to the remaining pigmentprotein complexes and acts as a filter for excitation energy, thereby contributing to the efficient photoprotection under HL. In addition, the role of Q B -non-reducing RCs of PSII in photoprotection of chlorina mutants was also examined Yamazaki 2010). In dark-adapted samples, we also identified the higher relative content of Q B -nonreducing RCs of PSII in ANK mutants (Table 1b).…”
Section: Imbalance Between Psii and Psi And Its Functional Consequencesmentioning
confidence: 80%
See 1 more Smart Citation
“…Alternatively, Štroch et al (2004) found that the substantial part of the xanthophyll cycle pigments in chlorina f2 mutant of barley was not bound to the remaining pigmentprotein complexes and acts as a filter for excitation energy, thereby contributing to the efficient photoprotection under HL. In addition, the role of Q B -non-reducing RCs of PSII in photoprotection of chlorina mutants was also examined Yamazaki 2010). In dark-adapted samples, we also identified the higher relative content of Q B -nonreducing RCs of PSII in ANK mutants (Table 1b).…”
Section: Imbalance Between Psii and Psi And Its Functional Consequencesmentioning
confidence: 80%
“…Similar to our results, found in chlorina mutants of rice about 50 % of inactive PSII RCs compared to 20 % in WT. Yamazaki (2010) examined the PSII heterogeneity in chlorina mutants in different light conditions. He found that mutant plants regulate their stoichiometry through the adjustment of the contribution of active PSII RCs.…”
Section: Imbalance Between Psii and Psi And Its Functional Consequencesmentioning
confidence: 99%
“…28,–30 Due to the large difference in antenna size, photoreduction of Q A in PSIIa proceeds more rapidly than in PSIIβ for DCMU-infiltrated thylakoids. 31 Fluorescence of chl- a in green algae has also been found to be spatially heterogeneous, 12,32 which may be interpreted in terms of the heterogeneity of the PSIIα/β process.…”
Section: Chlorophyll Fluorescencementioning
confidence: 98%
“…Accordingly, differences in leaf coloration have been observed between Chl-deficient mutants and the corresponding wild-type plants in species such as Arabidopsis thaliana, Gingko biloba, and Oryza sativa. Previous studies have identified two types of Chl-deficient rice mutant, which are based on the ratio of Chl a to Chl b, namely, type 1, in which Chl b is completely absent (Chl b-lacking mutants), and type 2, characterized by high Chl a/b ratios of between approximately −10 and −15 (Chl b-deficient mutant) [41,42,50]. Moreover, a study indicated that the Chl a/b in ch11 slightly fluctuated from 9 to 11 in 6 days incubation in various irradiances [50].…”
Section: Pigment Contents and Chloroplast Developmentmentioning
confidence: 99%
“…Previous studies have identified two types of Chl-deficient rice mutant, which are based on the ratio of Chl a to Chl b, namely, type 1, in which Chl b is completely absent (Chl b-lacking mutants), and type 2, characterized by high Chl a/b ratios of between approximately −10 and −15 (Chl b-deficient mutant) [41,42,50]. Moreover, a study indicated that the Chl a/b in ch11 slightly fluctuated from 9 to 11 in 6 days incubation in various irradiances [50]. In our previous study, we observed reductions in Chl content, an absence of Chl b, and abnormal chloroplast development in Chl b-lacking mutants, which were characterized by light green leaves compared with the dark green pigmentation seen in the leaves of wild-type plants [26].…”
Section: Pigment Contents and Chloroplast Developmentmentioning
confidence: 99%